Методи діагностування інтерактивних обчислювальних мереж, що реконфігуруються на функціональних модулях, що програмуються - Лобойченко, Д. А. (ХНУРЕ, 2023)
The work will create models and methods tor modifying unidirectional iterative networks and synthesizing checking sequences; creation of methods for the synthesis of testing tests using cyclic and characteristic symbols of automaton models of nodes, which allow formalizing and simplifying the procedure for generating tests with built-in diagnostic tools and checking the health of the entire network, eliminating the labor-intensive procedure for modeling faults.